The Effect of Financial Services Authority Regulatory Implementation Concerning Financial Consumer Protection on Banking Financial Performance - Fredi Wijaya Kusuma (Eduvest - Journal of Universal Studies, 2023)
Many parties engage in banking as the financial services industry grows, particularly in Indonesia. To keep banks safe, financial services must emphasize customer protection. The Financial Services Authority (OJK), Indonesia's financial services regulator, implemented several consumer protection measures. The policy may hurt banks despite protecting customers. Consumer protection laws strengthen banks. Proper protection would make clients feel safer and increase bank trust. Banks with strong consumer protection regulations will attract more clients since customers will feel safe doing so. This study examines how the OJK regulation's implementation on financial services consumer protection affected national commercial banks' financial performance from 2017 to 2021. This study adopts descriptive and verifiative approaches to analyze 93 national commercial banks in Indonesia from 2017 to 2021. The research utilizes secondary data from the Financial Services Authority (OJK) and bank financial statements. The investigations done have led to the conclusion that implementing consumer protection can improve bank financial performance and lower credit risk